Competitiveness of Indonesia Palm Oil in the International Market - Susilowati, Indah; Puji Setyowati, Etma; Akhmad Al Barabasi, Haidar; Naeni Nur Khaeni, Siti (Universitas Negeri Semarang, 2025)
Indonesia is the largest exporter of palm oil in the world. The growth of production and exports and the decreasing of import Indonesia palm oil should also increases the competitiveness of Indonesia palm oil in the International market. Therefore, We need to know the competitiveness of palm oil in Indonesia by calculate the value of export, production, and import through descriptive method model analysis using Import Dependency Ratio (IDR), Self Sufficiency Ratio (SSR), and Revealed Comparative Advantage (RCA) as the analysis tools. The data we used in this research is secondary data from Central Bureau of Statistic and UN Comtrade year 1990 until 2022.